(untitled) (Journal of Parents and Teachers, 2014)
School leadership, rather than focusing on administrative tasks and management, must focus on what is the central mission of the school: improving student learning. That requires making schools learning communities for teachers themselves, with a distributed or shared leadership that can empower teachers.